menu
QAmmunity.org
Login
Register
My account
Edit my Profile
Private messages
My favorites
Register
Ask a Question
Questions
Unanswered
Tags
Categories
Ask a Question
12 = -4(-6x – 3) a. -1 b. 0 c. 1 d. 2
asked
Dec 18, 2017
192k
views
1
vote
12 = -4(-6x – 3)
a. -1
b. 0
c. 1
d. 2
Mathematics
high-school
Polat Tuzla
asked
by
Polat Tuzla
6.4k
points
answer
comment
share this
share
0 Comments
Please
log in
or
register
to add a comment.
Please
log in
or
register
to answer this question.
2
Answers
3
votes
12 = -4 * (-6x - 3)
(12) / -4 = (-4 * (-6x - 3)) / -4
-3 = -6x - 3
(-3) + 3 = (-6x - 3) + 3
0 = -6x
0/-6 = (-6x) / -6
0 = x
Final Answer:
b. x = 0
Hope I helped :)
EdHuamani
answered
Dec 21, 2017
by
EdHuamani
7.7k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
2
votes
The right answer would be A
Big Green Alligator
answered
Dec 23, 2017
by
Big Green Alligator
6.4k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
Ask a Question
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.
7.4m
questions
9.9m
answers
Other Questions
How do you estimate of 4 5/8 X 1/3
Write words to match the expression. 24- ( 6+3)
Please solve the following equation. x-6x=56
whats the most accurate estimation of 65+77
Find the additive inverse of 18/23
Twitter
WhatsApp
Facebook
Reddit
LinkedIn
Email
Link Copied!
Copy
Search QAmmunity.org